The ones who don't say they love you : stories - Ruffin, Maurice Carlos (One World, 2021)
"Maurice Carlos Ruffin has an uncanny ability to create spaces. These perspectival, character-driven stories center on the margins and are deeply rooted in New Orleanian culture. In "Beg Borrow Steal," a boy relishes time spent helping his father find work after just coming home from prison; in "Ghetto University," a couple whose been struggling financially turn to crime after hitting rock bottom; in "Before I Let You Go," a woman who's been in NOLA for generations fights to keep her home; in "Fast hands, Fast Feet," an army vet and a runaway teen find companionship while sleeping under a bridge; in "Mercury Forges," a flash fiction piece among several in the collection, a group of men hurriedly make their way to a home where an elderly gentleman lives, trying to reach him before the water from Hurricane Katrina does; and in the title story, a young man works the street corners of the French Quarter, trying to achieve a freedom not meant for him"--